Disease on Nursery Stock as Affected by Environmental Factors and Seasonal Inoculum Levels of Phytophthora ramorum in Stream Water Used for Irrigation - Tjosvold, S A (Plant disease, 2008)
A pear bait monitoring system was used to detect and quantify Phytophthora ramorum propagules in streams that flow through woodland areas with sudden oak death in Santa Cruz County, CA from 2001 to 2007. Stream propagules were detected most frequently or occurred in highest concentrations in winter and spring. The stream propagule concentration was characterized with statistical models using temperature and rainfall variables from 2004 to 2007. The highest concentrations of propagules occurred when stream sampling was preceded by about 2 months with low maximum daily temperatures and by 4 days with high rainfall. The occurrence of propagules in streams in the summer was mostly associated with infected leaves from the native host Umbellaria californica that prematurely abscised and fell into the water. When the stream water was used for irrigating rhododendron nursery stock from 2004 to 2007, disease occurred only three times in the two wettest springs (2005 and 2006) on plants sprinkler irrigated with stream water with relatively high concentrations of propagules. Disease incidence was described with a statistical model using the concentration of infective propagules as measured by pear baiting and consecutive hours of leaf wetness measured by electronic sensors at rhododendron height. The concentration of infective propagules was significantly reduced after water was pumped from the stream and applied through sprinklers